2017
DOI: 10.1007/s13770-016-0010-5
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular Xenotransplantation of Adipose-Derived Stromal Cells to Treat Osteoarthritis in a Goat Model

Abstract: Adipose-derived stromal cells (ASCs) have been investigated as a cell source for tissue regeneration. The purpose of this study was first to confirm if medial meniscectomy induces osteoarthritis (OA) in goats within a relative short period of time, and more importantly, to investigate if systemic treatment with immunosuppressive drugs is necessary in intra-articular ASC xenotransplantation for successful regeneration of articular cartilage and prevention of joint inflammation. Eight Korean native black goats 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…However, cell therapy using ASCs is preferred because these cells are easy to isolate and have high relative abundance than BM-MSCs [9]. Moreover, studies suggest that transplanted ASCs accelerate wound healing by expanding the fibroblasts phenotype and increasing the supply of macrophages to the wound, enhancing granulation tissue formation [10][11][12]. Further studies showed that ASCs promote the growth of dermal fibroblasts through not only intercellular cell-to-cell contact, but also by paracrine activation of marginal cells [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, cell therapy using ASCs is preferred because these cells are easy to isolate and have high relative abundance than BM-MSCs [9]. Moreover, studies suggest that transplanted ASCs accelerate wound healing by expanding the fibroblasts phenotype and increasing the supply of macrophages to the wound, enhancing granulation tissue formation [10][11][12]. Further studies showed that ASCs promote the growth of dermal fibroblasts through not only intercellular cell-to-cell contact, but also by paracrine activation of marginal cells [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Human adipose stem cells (hASCs) are known to prolong the survival of ASCs and enhance anti-inflammatory effect [23]. The author has also tested if injection of hASCs in spheroid form could prolong the survival of ASCs in the joint cavity of immunosuppressed rats.…”
Section: Rationale For Intra-articular Injection Therapy In Osteoarthmentioning
confidence: 99%
“…Nonviral, adenoviral, retroviral, and adeno‐associated virus (AAV) vectors have been used to deliver genes to AC defects using ex vivo approaches . While most studies were performed in small animals such as rats and rabbits, data from large animal (sheep or horse), which would be more predictive of human results are generally lacking …”
Section: Gene‐enhanced Cartilage Regenerationmentioning
confidence: 99%
“…2 While most studies were performed in small animals such as rats and rabbits, data from large animal (sheep or horse), which would be more predictive of human results are generally lacking. 39 Gene Transfer of GFs for Cartilage Regeneration Gene transfer of GFs makes transduced cells secrete active peptides that can produce a more favorable environment for cartilage regeneration. Genes that would stimulate chondrogenesis or inhibit AC degeneration can be used with this type of gene therapy.…”
Section: Vectors For Gene Transfermentioning
confidence: 99%